The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1093/cid/ciac314
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hospitalized Coronavirus Disease 2019 and Influenza Patients Requiring Supplemental Oxygen in a Cohort Study: Clinical Impact and Resource Consumption

Abstract: Background To compare clinical characteristics, outcomes, and resource consumption of patients with COVID-19 and seasonal influenza requiring supplemental oxygen. Methods Retrospective cohort study conducted at a tertiary-care hospital. Patients admitted due to seasonal influenza between 2017 and 2019, or with COVID-19 between March and May 2020 requiring supplemental oxygen were compared. Primary outcome: 30-day mortality. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Despite numerous uncertainties, SARS-CoV-2, specifically the Omicron (B.1.1.529) variant, influenza virus and RSV, may have similarities in terms of symptoms, immune responses, laboratory parameters, the mean viral loads of affected individuals [ 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 ], the rate of asymptomatic infections and the protective effect of face masks [ 111 , 112 ], although the duration of viral shedding may be longest in SARS-CoV-2 infections [ 78 , 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite numerous uncertainties, SARS-CoV-2, specifically the Omicron (B.1.1.529) variant, influenza virus and RSV, may have similarities in terms of symptoms, immune responses, laboratory parameters, the mean viral loads of affected individuals [ 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 ], the rate of asymptomatic infections and the protective effect of face masks [ 111 , 112 ], although the duration of viral shedding may be longest in SARS-CoV-2 infections [ 78 , 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients in the pre-omicron group were younger and had fewer comorbidities than those in the remaining groups, consistent with the results of studies conducted during the initial stages of the pandemic. 11 12 13 14 15 16 Conversely, the baseline characteristics were similar between the omicron and influenza groups, with almost half of the patients aged ≥ 70 years and a high prevalence of comorbidities. The age distribution and prevalence of comorbidities varied among patients with the omicron variant and those with previous COVID-19 variants.…”
Section: Dicussionmentioning
confidence: 98%
“…Furthermore, these studies showed conflicting results, with some indicating a higher prevalence of dyspnea in COVID-19 or influenza and other demonstrating no significant differences. 15 25 26 A Korean study found that dyspnea affected 10.6% and 23.4% of patients with pneumonia caused by COVID-19 and influenza, respectively. However, the study only investigated dyspnea of New York Heart Association class 2 or higher.…”
Section: Dicussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Almost, all public health restrictions have now been lifted and this could increase the likelihood of more respiratory virus co-infections during future winters, substantially straining the available healthcare resources. 19 , 20 Interestingly, it is reported that influenza vaccination may be associated with a reduced risk of SARS-CoV-2 infection. 21 These results lend support to the importance of continuing vaccinating against Covid-19 as well as against Influenza.…”
mentioning
confidence: 99%